PENGARUH RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2013 - Hj. Dewi Rejeki, SE., Ak., M.Si., CA. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The purpose of this study is to determine how much are liquidity ratio and profitability ratio claim influence to going concern audit opinion in manufactured companies listing in Indonesian Securities Exchange. Source of data in this study is secondary data. The population of data is manufactured companies listing in Indonesian Securities Exchange and the sample of data are manufactured companies listing in Indonesia Securities Exchange for 5 (five) years which are from 2009 until 2013. Samples data are taken by using of purposive sampling method. The method of data analysis is using descriptive statistics and double regression analysis. This data analyzed by SPSS which are Partialy and Simultaneously Regression test. The result of this study showed that Liquidity ratio and Profitability ratio are partialy and simultaneously had a negative influences to Going Concern Audit Opinion in manufactured companies which are listing in Indonesian Securities Exchange for 5 (five) years.